DIFFERENCE URINARY INCONTINENCE BEFORE AND AFTER CONDUCTED MASSAGE, KEGEL EXERCISE IN ELDERLY PATIENTS AT PUBLIC HOSPITALS SEMBIRING DELI TUA - Rahmad Gurusinga; Elsaria Br Sembiring (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2018)
Urinary Incontinence is involuntary urination, or leakage of urinary that is very real and pose a social. High incidence rates urinary incontinence causes the need for treatment with massage, kegel exercise aimed at rebuilding pelvic floor muscle strength. The purpose of this study was to determine whether there is a difference in urinary incontinence before and after the massage, kegel exercise in elderly patients in public hospitals deliberate delitua in 2018. The study design used is quasy experiment, using the design of pre-test and post-test control group design. Population and samples used in this study were 15 elderly who have urinary incontinence taken by accidental sampling. Based on the result of statistical test by using T-test with paired sample T-test obtained dat analysis showed that based on age af patient based on age patient urinary incontinence most aged 60-65 years (66,7%), while at age 66-70 (20,0%), and at least 71-74 (13,3%). Can be known urinary incontinence before given massage, kegel exercise counted 14 people (93,3%) medium incontinence and as many as 1 person (6,7%) severe incontinence. After given message, kegel exercise can be seen that there are descrease that is as much as 7 people (46,7%) light incontinence and as many as 8 people (53,3%) medium incontinence. The conclusions of these result indicate that there is an effect of massage, kegel exercise to urinary incontinence in elderly patients in public hospitals deliberate delitua.